Ghrelin improves small intestinal barrier damage in sepsis by promoting miR-143/ATG2B-mediated autophagy - Jingquan Liu; Kai Shi; Hanhui Cai; Zihao Zheng; Bin Fan; Xianghong Yang; Ziqiang Shao (PLoS ONE, 2025)
Intestinal barrier damage is crucial for the development of sepsis. Ghrelin (GHS) can restore intestinal barrier function. However, the mechanisms of GHS on intestinal barrier damage in sepsis remain unclear. We aimed to explore the mechanisms of GHS against intestinal barrier damage in sepsis. Septic models were established by cecal ligation and puncture surgery for rats and lipopolysaccharides exposure for IEC-6 cells. Furthermore, these septic models were overexpressed miR-143 and treated with GHS. In vivo, small intestinal pathological injury and D-lactic acid level were detected. Tight junction protein (Claudin-1, Occludin and ZO-1) expressions and autophagosome number were evaluated. In vitro, cell viability, autolysosome number, and relationship between miR-143 and ATG2B were determined. miR-143, ATG2B and autophagy-related protein (Beclin-1, p62 and LC3I/LC3II) levels were evaluated in rats and cells. GHS mitigated small intestinal pathological injury and decreased D-lactic acid level for septic rats. Additionally, GHS elevated tight junction protein expressions, ATG2B, Beclin-1 and LC3I/LC3II levels, and autophagosome number, but reduced miR-143 and p62 levels for septic rats. However, miR-143 overexpression presented the opposite results. Consistently, cellular experiments found that GHS increased cell viability, autolysosome number, and presented similar results for miR-143, ATG2B and autophagy-related protein levels for lipopolysaccharides-exposed cells. Additionally, ATG2B directly targeted miR-143 in IEC-6 cells. Both animal and cellular experiments found the effects of GHS on sepsis-induced small intestinal barrier damage were reversed by miR-143 overexpression. GHS may improve small intestinal barrier damage in sepsis through miR-143/ATG2B-mediated autophagy, indicating miR-143/ATG2B was an underlying therapeutic target for sepsis.